A Comparison of Domestic and International Human Resource Management Practices from an Organizational Culture Perspective: A Case Study of the Retail Companies Indomaret and 7-Eleven - Gustian Audi; Khusnul Hotimah; Floryan Floryan; Dian Prihardini Wibawa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the comparison of Human Resource Management implementation at the domestic and international levels by looking at the organizational culture through case studies of Indomaret and 7-Eleven retail companies. Different cultural contexts, operational sizes, and managerial approaches are crucial elements that influence the design and implementation of HRM policies in both companies. This study uses a literature review method with a comparative case study approach, taking secondary data from academic journals, reference books, and official company documents. The scope of the study covers practices in recruitment and selection, training and development programs, performance appraisals, and reward systems related to organizational cultural values. The results of this study indicate that the human resource management approach applied at Indomaret as a domestic retail company tends to focus on internal stability, compliance with existing procedures, and uniformity in work behavior. This reflects a hierarchical and collective organizational culture. In contrast, 7-Eleven, an international retail company, adopts more flexible and responsive HRM practices by combining international standards with adjustments to local culture. This study states that organizational culture plays an important role in creating differences between human resource management practices at the domestic and international levels and is a major factor in achieving organizational effectiveness.